Biotechnology-based therapy for stroke treatment: review - Utama, Hieronimus Adiyoga Nareswara; Mariya, Sela Septima; Dumingan, Alvian; Putri, Ratih Rinendya; Sunarno, Sunarno; Malik, Amarila (JURNAL ILMU KEFARMASIAN INDONESIA, 2024)
Various therapeutic agents have been used to treat stroke. However, currently there is extensive exploration of new potential therapies for stroke involving novel signaling pathways and development of therapeutic agents through biotechnological approaches. This article examines the recent advances in stroke therapy using biotechnology-based drugs. We conducted a comprehensive search using specific keywords relating to Ischemic Stroke, ATMP, Peptide, Antibody, Stem Cells, and connected topics in the databases of Medline, Scopus, Web of Science, and Pubmed. The main focus of the selection criteria was on English-language literature that explored the relationship between Ischemic Stroke, ATMP, Peptide, Antibody, Stem Cells, and related factors. This article exhibits that numerous studies are being conducted and have demonstrated the use of biotechnology-based therapeutic agents for stroke, including tissue plasminogen activators, therapeutic peptides, microRNA, monoclonal antibodies, as well as stem cells. These therapeutic agents have not only been tested on test animals but have also been commenced to be tested in clinical studies or have obtained marketing approval for use in ischemic stroke patients. In conclusion, despite the limited number of approved drugs, advancements in biotechnology are poised to make them common adjunct treatments for stroke patients, not just for managing the disease but also for its cure and regenerative effects in survivors.